2022
DOI: 10.1371/journal.ppat.1010738
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of functional antibodies following acute Epstein-Barr virus infection

Abstract: While Epstein-Barr virus causes mostly asymptomatic infection, associated malignancies, and autoimmune and lymphoproliferative diseases occur. To dissect the evolution of humoral immune responses over the course of EBV infection and to gain a better understanding of the potential contribution of antibody (Ab) function to viral control, we comprehensively profiled Ab specificities and Fc-functionalities using systems serology and VirScan. Ab functions against two early (p18 and p47/54) and two latent (gp350/220… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 49 publications
0
10
0
Order By: Relevance
“…A recent study ( 46 ) showed that, in addition to EBV EA-D antibody responses, seropositivity of EBV envelope glycoproteins gp42 and gp350, which are essential for EBV lytic infection of B cells, were enriched in participants with LC ( 46 ). These EBV envelope proteins are targets of neutralizing antibodies ( 47 ) and, in the case of gp350, may be short-lived in circulation, suggesting recent viral activity prior to or following the development of LC.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study ( 46 ) showed that, in addition to EBV EA-D antibody responses, seropositivity of EBV envelope glycoproteins gp42 and gp350, which are essential for EBV lytic infection of B cells, were enriched in participants with LC ( 46 ). These EBV envelope proteins are targets of neutralizing antibodies ( 47 ) and, in the case of gp350, may be short-lived in circulation, suggesting recent viral activity prior to or following the development of LC.…”
Section: Discussionmentioning
confidence: 99%
“…Serological evidence of EBV-specific antibodies is important evidence for diagnosis of EBV-IM. The most valuable serological finding is anti-virus-capsid antigens (VCA)-IgM antibodies against EBV, which is considered confirmatory for acute primary EBV infection ( Karsten et al, 2022 ; Ceraulo & Bytomski, 2019a ). In our study, all patients had active infection as confirmed by detection of the causative organism within 72 h of admission or by detection of EBV-IgM or IgM antibodies to other pathogens.…”
Section: Discussionmentioning
confidence: 99%
“…Its well-regulated and spatially separated viral antigen expression elicits a diverse range of antibodies, which not only play a key role in the host's defense against EBV infection, but also reflect the activity of both the virus and the host's immune response. 5 Research has shown that EBV antibodies can be effective indicators of various EBV-associated malignancies. 117 While elevated serum anti-EBV IgA is generally associated with an increased risk of EBV-associated epithelial tumors, elevated serum anti-EBV IgG indicates an increased risk of EBV-associated lymphoid tumors.…”
Section: Prospectsmentioning
confidence: 99%
“…EBV encodes more than 80 viral proteins that participate in virion structure formation and regulate the latent‐lytic EBV life cycle 2,3 . The immune system of an infected host generates a diverse range of antibodies against EBV‐encoded proteins with different subtypes, durations, and functions 4,5 . These antibodies can provide insights into the epidemiology of EBV‐associated diseases and contribute to our understanding of EBV pathology 4 …”
Section: Introductionmentioning
confidence: 99%